Metal-free catalyst ZrC whisker as well as preparation method and application thereof
ZrC whiskers are prepared by electrospinning and high-temperature carbonization methods without metal catalysts, which solves impurities and whisker damage caused by metal catalysts, and realizes a high-purity and low-cost preparation process, which improves the quality and application potential of the material.
Patent Information
- Application Number
- CN202411704150.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-02-25
AI Technical Summary
The use of metal catalysts in the existing methods for preparing ZrC whiskers results in a catalyst on top of the whiskers, and the metal catalyst is an impurity, affecting the material matrix, and the removal process may damage the whiskers.
ZrC whiskers are prepared by electrospinning using a metal-free catalyst method, and metal salt solutions are prepared using zirconium sources, sodium fluoride and carbon sources (such as polyacrylonitrile or polyvinylpyrrolidone), and spinning and high-temperature carbonization are carried out to achieve the growth of whiskers.
High-purity, impurity-free ZrC whisker preparation is achieved, avoiding the influence of metal catalysts on the matrix, simplifying the preparation process, reducing costs, and improving the quality and application prospects of whiskers.
Smart Images

Figure CN119507052A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ultra-high temperature ceramic materials, and in particular relates to a metal-free catalyst ZrC whisker and a preparation method and application thereof. Background Art
[0002] Zirconium carbide ZrC, as an ultra-high temperature ceramic material, has a higher melting point, higher hardness and better chemical stability than SiC and C fibers. Due to its lattice structure, ZrC has the advantages of both ceramics and metals, so it has broad application prospects in ultra-high temperature ceramics, wave absorption, etc. Its one-dimensional structure, such as fiber and whisker, has more excellent mechanical and ablation resistance, among which the high strength and special structure of whisker can be used as a reinforcement to combine closely with the matrix, and improve the mechanical and oxidation resistance of the material by hindering crack deflection.
[0003] Currently, most ZrC whiskers are prepared by adding metal catalysts to promote whisker growth. For example, the Chinese invention patent application with publication number CN117926384A obtains a ternary mixed system by mixing Ni powder, zirconium powder and carbon powder evenly by ball milling, and then obtains ZrC whiskers after heat treatment at 960~1150℃. This method can produce whiskers with needle-shaped tips.
[0004] In the literature 1 “Study on the synthesis and growth mechanisms of therefractory ZrC whiskers, Liang Xu, Chuanzhen Huang, Hanlian Liu, Bin Zhou, Hongtao Zhu, Guolong Zhao, Jun Wang. Int. Journal of Refractory Metals and Hard Marerials, 2014, 42: 116-119”, the authors used zirconium oxide, C, Ni, and NaF as raw materials to prepare ZrC whiskers by carbothermal reduction. In reference 2 "Synthesis of zirconium carbide whiskers by combination of microwave hydrothermal and carbonthermal reduction, Kezhi Li, Xuan Zhou, Zhigang Zhao, Chunyu Chen, Chang cong Wnag, Biyun Ren, LriLei Zhang. Journal of Solid State Chemistry, 2018, 258: 383-390", the authors used zirconium oxychloride, sucrose, NaOH, NiCl2 and NaF as raw materials to prepare ZrC whiskers by microwave hydrothermal and carbon thermal reduction. The whiskers prepared by this method have a relatively large length diameter and are in the form of cylinders and pagodas. However, this method uses more raw materials and is somewhat dangerous and the procedure is more complicated.
[0005] In summary, when the existing preparation methods prepare whiskers by adding metal catalysts, the whiskers mostly grow by the VLS (gas-liquid-solid) mechanism, so there are often catalysts on the top of the whiskers, and sometimes the top metal droplets will slide to the bottom of the whiskers and affect the whiskers and the matrix. When using metal catalysts, regardless of the morphology of the whiskers obtained, the metal catalysts will be impurities in most cases. For example, when used in a high-temperature environment, the high activity of the metal catalyst may affect the material matrix, so further impurity removal may be required during use, and this process may damage the whiskers and affect their quality. Summary of the invention
[0006] In order to overcome the shortcomings of the above-mentioned prior art, the purpose of the present invention is to provide a metal-free catalyst ZrC whisker and a preparation method and application thereof. Since there is no metal catalyst, the method prepares ZrC whiskers by VS (gas-solid) mechanism growth, there is no liquid phase involved in the whisker growth, there is no impurity and the purity is high, and large-scale and simple preparation of ZrC whiskers can be achieved.
[0007] In order to achieve the above object, the present invention adopts the following technical solutions: The present invention provides a method for preparing a metal-free catalyst ZrC whisker, comprising the following steps: Dissolve the zirconium source and sodium fluoride in NN, dimethylformamide to prepare a metal salt solution; Adding a carbon source into a metal salt solution to obtain a spinning precursor solution; wherein the carbon source is used as both a carbon source and a spinning aid, and the carbon source is polyacrylonitrile or polyvinyl pyrrolidone; Electrospinning is performed using a spinning precursor solution to obtain primary spinning fibers; The initial spinning is carbonized at high temperature to obtain ZrC whiskers.
[0008] In one embodiment, the zirconium source is any one of zirconium tetrachloride, zirconium oxychloride and zirconium acetylacetonate.
[0009] In one embodiment, the mass ratio of the zirconium source to sodium fluoride is 1:(0.1-1.5).
[0010] In one embodiment, the mass ratio of the sum of the mass of the zirconium source and sodium fluoride to the mass of NN, dimethylformamide is (1-3.5):7.
[0011] In one embodiment, the mass ratio of the carbon source to the zirconium source is (0.5-2.5):1.
[0012] In one embodiment, the electrospinning process parameters are as follows: The receiving distance is 10~15cm, the spinning voltage is 15kV~21kV, the propulsion speed is 7μL / min, and the rotation speed of the drum receiver is 500rpm.
[0013] In one embodiment, the high temperature carbonization process is as follows: From room temperature, increase the temperature to 1000℃ at a rate of 10℃ / min below 1000℃. After reaching 1000℃, increase the temperature to 1400℃~1600℃ at a rate of 5℃ / min and keep it at this temperature for 2h.
[0014] In one embodiment, the average molecular weight of the carbon source is 1,500,000.
[0015] The present invention also provides a ZrC whisker prepared according to the above method for preparing the ZrC whisker without metal catalyst.
[0016] The present invention also provides an application of the ZrC whisker in coatings, aerospace and heat storage and thermal insulation products.
[0017] Compared with the prior art, the present invention has the following beneficial effects: The present invention uses an electrostatic spinning method to prepare a one-dimensional fiber structure of the initial spinning to provide a template, and the ZrC whisker can be obtained under carbon thermal reduction reaction conditions through the template. The raw materials used are simple and environmentally friendly, without the participation of hazardous drugs and metal catalysts, the electrostatic spinning operation is simple and convenient, and the obtained film-like initial spinning can subsequently become a template for whisker growth and may have a mesh structure, so as to solve the technical problems existing in the large-scale and simple preparation of ZrC whiskers. Traditionally, ZrC whiskers are grown by adding metal catalysts, such as Ni, through the VSL (gas-liquid-solid) method. The metal catalyst plays a role in inducing the formation of crystal nuclei in the system, but the metal catalyst often exists as an impurity, which will affect the matrix when used under high temperature conditions, and when it is unevenly distributed such as agglomeration, it will also affect the matrix. At the same time, if the metal catalyst is to be removed, it will usually damage the whisker itself and affect its quality. The above preparation method does not require the addition of metal catalysts, only NaF is needed. Halogen compounds can help reduce the activation energy and eutectic temperature of one-dimensional material growth, form ZrF4 gas when heated, promote whisker growth, and whiskers grow in VS (gas-solid) mode. As the temperature rises, the NaF in the material overflows in the form of gas, and finally high-purity single-phase ZrC whiskers are obtained. At the same time, the method has good spinnability. After uniform stirring, the precursor fiber, i.e., initial spinning, is obtained by electrospinning. Since there is no metal catalyst, there will be no catalyst on the top of the whisker and the metal droplets on the top will not slide to the bottom of the whisker, and there will be no impurities. When used in a high-temperature environment, the high activity of the metal catalyst will not affect the material matrix, will not damage the whiskers, and will not affect their quality, and can achieve large-scale and simple preparation of ZrC whiskers.
[0018] Furthermore, the present invention uses ZrCl4, zirconium acetylacetonate, zirconium oxychloride, etc. as zirconium sources, PAN or PVP as carbon sources and spinning aids, the raw material cost is low, and it is green and environmentally friendly, the experimental process is relatively stable, the electrospinning equipment is simple, the cost is low, and the operation is simple. At the same time, the length and quantity of ZrC whiskers can be controlled by the spinning voltage, spinning distance, and NaF addition amount. ZrC whiskers are obtained by high-temperature heat treatment, and the reaction cycle is short.
[0019] The ZrC whiskers prepared by the present invention have low cost and simple preparation process, and have broad application prospects in coatings, aerospace, heat storage and thermal insulation, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 is a SEM image of the precursor fiber morphology obtained in Example 1; Figure 2 is the XRD pattern of the whisker synthesized in Example 1 after heat treatment at 1600°C; Figure 3 a) is a SEM image of the ZrC whisker synthesized in Example 1; Figure 3 b) is a SEM image of the ZrC whisker synthesized in Example 2; Figure 4 a) is a TEM image of the ZrC whisker synthesized in Example 1, Figure 4 b) and Figure 4 c) is the mapping diagram of the whisker. DETAILED DESCRIPTION
[0021] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.
[0022] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.
[0023] In this article, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values within the range (including integers and fractions).
[0024] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”
[0025] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.
[0026] The invention provides a metal-free catalyst ZrC whisker and a preparation method and application thereof.
[0027] The preparation method comprises the following steps: 1) dissolving zirconium tetrachloride, zirconium oxychloride and zirconium acetylacetonate as zirconium sources in NN-dimethylformamide (DMF), adding a certain amount of sodium fluoride NaF to promote the growth of ZrC whiskers, and preparing a metal salt solution; 2) placing the metal salt solution and a carbon source reagent in a glass bottle, and after sufficient stirring, obtaining a spinning precursor solution; the carbon source reagent is polyacrylonitrile (PAN) or polyvinyl pyrrolidone (PVP), and also serves as a spinning aid to provide viscosity; 3) performing electrostatic spinning under preset spinning process conditions to obtain primary spinning. 4) performing high-temperature carbonization on the primary spinning to obtain ZrC whiskers.
[0028] Among them, the mass ratio of the zirconium source and sodium fluoride is 1: (0.1~1.5), the mass ratio of the carbon source and the zirconium source is (0.5~2.5):1, and the mass ratio of the sum of the mass of the zirconium source and sodium fluoride to NN and dimethylformamide is (1~3.5):7.
[0029] The specific spinning process is as follows: the receiving distance is 10~15cm, the spinning voltage is 15kV~21kV, the propulsion speed is 7μl / min, the rotation speed of the roller receiver is 500rpm, and the average molecular weight of the carbon source (PAN) is 1500000.
[0030] The process of high-temperature carbonization is as follows: starting from room temperature, the temperature is increased from below 1000°C to 1000°C at a rate of 10°C / min, and after reaching 1000°C, the temperature is increased to 1400°C~1600°C at a rate of 5°C / min, and kept warm for 2h.
[0031] This method does not require the addition of spinning aids, greatly simplifies the preparation process, saves time and cost, and has high repeatability, easy raw materials, low process cost, and no need to add metal catalysts to promote whisker growth. The strength of single crystal whiskers is higher than that of fibers. As a reinforcement to improve the ultra-high temperature ceramic material itself, it can be used in coatings, aerospace and heat storage and insulation products, and can play a key role in the expanded application in the field of aerospace thermal protection.
[0032] The preparation method is simple and easy to control, has a certain aspect ratio and does not require the addition of metal catalysts, and is a ZrC whisker prepared by electrospinning and carbon thermal reduction. At the same time, the high strength, high melting point, and anti-oxidation and ablation characteristics of ZrC whiskers can be used in the field of ultra-high temperature thermal protection.
[0033] In addition, when the Zr source in the raw material is replaced with Hf, Ta, Ti, or Nb sources, the corresponding fibers can be obtained. At the same time, the corresponding impurity-free whiskers can be obtained by adding NaF and sintering without adding a metal catalyst.
[0034] The corresponding preparation method is as follows: 1) Dissolve any one of Hf source, Ta source, Ti source and Nb source in NN-dimethylformamide (DMF), add a certain amount of sodium fluoride NaF to promote the growth of ZrC whiskers, and prepare a metal salt solution; 2) Put the metal salt solution and carbon source reagent in a glass bottle, and after sufficient stirring, obtain a spinning precursor solution; the carbon source reagent is polyacrylonitrile (PAN) or polyvinyl pyrrolidone (PVP), which also serves as a spinning aid to provide viscosity; 3) Perform electrostatic spinning under preset spinning process conditions to obtain primary spinning. 4) The primary spinning is subjected to high-temperature carbonization to obtain whiskers.
[0035] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0036] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.
[0037] Embodiment 1: ① Weigh 1.0g of ZrCl4 as a zirconium source, add it to 10mL of DMF solvent, stir until uniform at room temperature, add 0.2g of NaF and stir evenly. Finally, add 1.0g of PAN as a carbon source and spinning aid, stir at room temperature until uniform to obtain a spinning precursor solution; ② The spinning precursor solution was spun using a standard electrospinning device, and the pre-spun fibers were collected on aluminum foil. The drum receiver speed was 500 rpm, the voltage during electrospinning was 15 kV, the propulsion speed was 7 μl / min, and the collection distance was 15 cm. After the electrospinning was completed, the precursor fibers were obtained; ③ Place the initially spun fibers in a graphite crucible, and then place the crucible in a vertical tubular furnace for heat treatment in an argon atmosphere, first raising the temperature to 1000°C at a rate of 10°C / min, then raising the temperature to 1400°C at a rate of 5°C / min, and then keeping the temperature for 2 hours.
[0038] Embodiment 2: ① Weigh 1.0 g of ZrCl4 as a zirconium source, add it to 10 mL of DMF solvent, stir at room temperature until uniform, add 1.5 g of NaF and stir evenly, then add 1.0 g of PAN as a carbon source and spinning aid at the same time, stir at room temperature until uniform to obtain a spinning precursor solution; ② The spinning precursor solution was spun using a standard electrospinning device, and the pre-spun fibers were collected on aluminum foil. The drum receiver speed was 500 rpm, the voltage during electrospinning was 15 kV, the propulsion speed was 7 μl / min, and the collection distance was 10 cm. After the electrospinning was completed, the precursor fibers were obtained; ③ Place the initially spun fibers in a graphite crucible, and then place the crucible in a vertical tubular furnace for heat treatment in an argon atmosphere, first raising the temperature to 1000°C at a rate of 10°C / min, then raising the temperature to 1400°C at a rate of 5°C / min, and then keeping the temperature for 2 hours.
[0039] Embodiment 3: ① Weigh 1.0 g of zirconium oxychloride as a zirconium source, add it to 10 mL of DMF solvent, stir it at room temperature until it is uniform, add 0.5 g of NaF and stir it evenly, then add 1.0 g of PAN as a carbon source and spinning aid at the same time, stir it at room temperature until it is uniform to obtain a spinning precursor solution; ② The spinning precursor solution was spun using a standard electrospinning device, and the pre-spun fibers were collected on aluminum foil. The drum receiver speed was 500 rpm, the voltage during electrospinning was 15 kV, the propulsion speed was 7 μl / min, and the collection distance was 12 cm. After the electrospinning was completed, the precursor fibers were obtained; ③ Place the initially spun fibers in a graphite crucible, and then place the crucible in a vertical tubular furnace for heat treatment in an argon atmosphere, first raising the temperature to 1000°C at a rate of 10°C / min, then raising the temperature to 1400°C at a rate of 5°C / min, and then keeping the temperature for 2 hours.
[0040] Embodiment 4: ① Weigh 1.0 g of zirconium acetylacetonate as a zirconium source, add it to 10 mL of DMF solvent, stir it at room temperature until it is uniform, add 1.0 g of NaF and stir it evenly, then add 1.0 g of PAN as a carbon source and spinning aid at the same time, stir it at room temperature until it is uniform to obtain a spinning precursor solution; ② The spinning precursor solution was spun using a standard electrospinning device, and the pre-spun fibers were collected on aluminum foil. The drum receiver speed was 500 rpm, the voltage during electrospinning was 21 kV, the propulsion speed was 7 μl / min, and the collection distance was 15 cm. After the electrospinning was completed, the precursor fibers were obtained; ③ Place the initially spun fibers in a graphite crucible, and then place the crucible in a vertical tubular furnace for heat treatment in an argon atmosphere, first raising the temperature to 1000°C at a rate of 10°C / min, then raising the temperature to 1400°C at a rate of 5°C / min, and then keeping the temperature for 2 hours.
[0041] Embodiment 5: ① Weigh 0.5 g of ZrCl4 as a zirconium source, add it to 10 mL of DMF solvent, stir at room temperature until uniform, add 0.5 g of NaF and stir evenly, then add 1.0 g of PAN as a carbon source and spinning aid at the same time, stir at room temperature until uniform to obtain a spinning precursor solution; ② The spinning precursor solution was spun using a standard electrospinning device, and the pre-spun fibers were collected on aluminum foil. The drum receiver speed was 500 rpm, the voltage during electrospinning was 21 kV, the propulsion speed was 7 μl / min, and the collection distance was 15 cm. After the electrospinning was completed, the precursor fibers were obtained; ③ Place the initially spun fibers in a graphite crucible, and then place the crucible in a vertical tubular furnace for heat treatment in an argon atmosphere, first raising the temperature to 1000°C at a rate of 10°C / min, then raising the temperature to 1600°C at a rate of 5°C / min, and then keeping the temperature for 2 hours.
[0042] Embodiment 6: ① Weigh 1.0 g of ZrCl4 as a zirconium source, add it to 10 mL of DMF solvent, stir at room temperature until uniform, add 0.5 g of NaF and stir evenly, then add 2.5 g of PVP as a carbon source and spinning aid at the same time, stir at room temperature until uniform to obtain a spinning precursor solution; ② The spinning precursor solution was spun using a standard electrospinning device, and the pre-spun fibers were collected on aluminum foil. The drum receiver speed was 500 rpm, the voltage during electrospinning was 18 kV, the propulsion speed was 7 μl / min, and the collection distance was 15 cm. After the electrospinning was completed, the precursor fibers were obtained; ③ The initially spun fibers were placed in a graphite crucible, which was then placed in a vertical tubular furnace for heat treatment in an argon atmosphere, first at a temperature of 10°C / min to 1000°C, then at a temperature of 5°C / min to 1600°C, and then kept warm for 2 hours.
[0043] Embodiment 7: ① Weigh 1.0 g of HfCl4 as a Hf source, add it to 10 mL of DMF solvent, stir at room temperature until uniform, add 0.5 g of NaF and stir evenly, then add 2.4 g of PVP as a carbon source and spinning aid at the same time, stir at room temperature until uniform to obtain a spinning precursor solution; ② The spinning precursor solution was spun using a standard electrospinning device, and the pre-spun fibers were collected on aluminum foil. The drum receiver speed was 500 rpm, the voltage during electrospinning was 18 kV, the propulsion speed was 7 μl / min, and the collection distance was 15 cm. After the electrospinning was completed, the precursor fibers were obtained; ③ The initially spun fibers were placed in a graphite crucible, which was then placed in a vertical tubular furnace for heat treatment in an argon atmosphere, first at a temperature of 10°C / min to 1000°C, then at a temperature of 5°C / min to 1600°C, and then kept warm for 2 hours.
[0044] Embodiment 8: ① Weigh 1.0 g of TaCl4 as a Ta source, add it to 10 mL of DMF solvent, stir at room temperature until uniform, add 0.5 g of NaF and stir evenly, then add 1.0 g of PAN as a carbon source and spinning aid at the same time, stir at room temperature until uniform to obtain a spinning precursor solution; ② The spinning precursor solution was spun using a standard electrospinning device, and the pre-spun fibers were collected on aluminum foil. The drum receiver speed was 500 rpm, the voltage during electrospinning was 18 kV, the propulsion speed was 7 μl / min, and the collection distance was 15 cm. After the electrospinning was completed, the precursor fibers were obtained; ③ The initially spun fibers were placed in a graphite crucible, which was then placed in a vertical tubular furnace for heat treatment in an argon atmosphere, first at a temperature of 10°C / min to 1000°C, then at a temperature of 5°C / min to 1600°C, and then kept warm for 2 hours.
[0045] Figure 1 This is a SEM image of the precursor fiber synthesized in Example 1. Through SEM characterization, it is observed that the fiber is relatively uniform as a whole, but there are particles wrapped on the fiber, which is a mixture of Na, F, and Zr.
[0046] Figure 2 This is the XRD pattern of the product after the precursor fiber synthesized in Example 1 was heat treated at 1600°C. The pattern shows that after heat treatment at 1600°C, the whiskers are composed of a single ZrC phase with good crystallinity and no other impurity phases are found, thus proving that the method for preparing ZrC whiskers has high purity.
[0047] Figure 3 a is a SEM image of the precursor fiber synthesized in Example 1 after heat treatment at 1600° C. Through SEM characterization, it is observed that ZrC whiskers are generated after heat treatment and have a certain aspect ratio. Figure 3 b is the SEM image of the product after the precursor fiber synthesized in Example 2 was heat treated at 1600°C. It can be seen that ZrC whiskers can be successfully synthesized under different experimental conditions, and their aspect ratio also changes with different NaF content.
[0048] Figure 4 This is a TEM image of the precursor fiber synthesized in Example 1 after heat treatment at 1600° C. Through TEM characterization, it was observed that the diameter of the ZrC whisker was 1-3 μm.
[0049] The above contents are only for explaining the technical idea of the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.
Claims
1. A method for preparing metal-free catalyst ZrC whiskers, characterized in that: The following steps are involved: Dissolve the zirconium source and sodium fluoride in NN, dimethylformamide to prepare a metal salt solution; Adding a carbon source into a metal salt solution to obtain a spinning precursor solution; wherein the carbon source is used as both a carbon source and a spinning aid, and the carbon source is polyacrylonitrile or polyvinyl pyrrolidone; Electrospinning is performed using a spinning precursor solution to obtain primary spinning fibers; The initial spinning is carbonized at high temperature to obtain ZrC whiskers.
2. The method for preparing the metal-free catalyst ZrC whisker according to claim 1, characterized in that: The zirconium source is any one of zirconium tetrachloride, zirconium oxychloride and zirconium acetylacetonate.
3. The method for preparing the metal-free catalyst ZrC whisker according to claim 1, characterized in that: The mass ratio of the zirconium source to sodium fluoride is 1:(0.1-1.5).
4. The method for preparing the metal-free catalyst ZrC whisker according to claim 1, characterized in that: The mass ratio of the sum of the mass of the zirconium source and sodium fluoride to the mass of NN and dimethylformamide is (1-3.5):
7.
5. The method for preparing the metal-free catalyst ZrC whisker according to claim 1, characterized in that: The mass ratio of the carbon source to the zirconium source is (0.5~2.5):
1.
6. The method for preparing metal-free catalyst ZrC whiskers according to claim 1, characterized in that: The process parameters of the electrospinning are as follows: The receiving distance is 10~15cm, the spinning voltage is 15kV~21kV, the propulsion speed is 7μL / min, and the rotation speed of the drum receiver is 500rpm.
7. The method for preparing metal-free catalyst ZrC whiskers according to claim 1, characterized in that: The process of high temperature carbonization is as follows: From room temperature, increase the temperature to 1000°C at a rate of 10°C / min, then increase the temperature to 1400°C~1600°C at a rate of 5°C / min, and keep it at this temperature for 2h.
8. The method for preparing metal-free catalyst ZrC whiskers according to claim 1, characterized in that: The average molecular weight of the carbon source is 1500000.
9. ZrC whiskers prepared according to the method for preparing metal-free catalyst ZrC whiskers according to any one of claims 1 to 8.
10. Use of the ZrC whisker according to claim 9 in coatings, aerospace and heat storage and thermal insulation products.
Citation Information
Patent Citations
Zirconium carbide whisker and preparation method thereof
CN117926384A
Cited By
Fiber-like nanofiber wave-absorbing material and preparation method thereof
CN120138844A
Optical fiber-like nanofiber wave-absorbing material and preparation method thereof
CN120138844B